2013
DOI: 10.1080/09712119.2013.822810
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular fat and fatty acid profile of muscle of lambs finished in irrigated pasture

Abstract: The aim of this research was to study the differences between breeds through the analyses of the intramuscular fat content and fatty acid profile of the main local hair sheep breeds of Brazil, Morada Nova (MO), Brazilian Somali (SO) and Santa Ineˆs (SI) and the crossbred ½ Dorper )½ Morada Nova (F1). Genetic group was a significant source of variation for intramuscular fat content, individual fatty acids, polyunsaturated fatty acid (PUFA)/ saturated fatty acid (SFA) ratio, total PUFA, essential fatty acids (EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…The tendency of higher C18:1n9c and lower C18:0 in FC than in the two yak groups indicates the high activity of delta-9 desaturase and high fat anabolism ( 79 ), which is consistent with the higher fat content in FC. It is also consistent with the report of Lobo et al that genotype plays an important role in body fat anabolism ( 80 ). Lower concentrations of linoleic and linolelaidic acids (C18:2n6c and n6t) were observed in the meat of GY than in FC and FY, which was due to the lower content of C18:2 in grass than in concentrate feed ( 81 ), as C18:2n6c in meat is derived wholly from dietary intake ( 82 ).…”
Section: Discussionsupporting
confidence: 93%
“…The tendency of higher C18:1n9c and lower C18:0 in FC than in the two yak groups indicates the high activity of delta-9 desaturase and high fat anabolism ( 79 ), which is consistent with the higher fat content in FC. It is also consistent with the report of Lobo et al that genotype plays an important role in body fat anabolism ( 80 ). Lower concentrations of linoleic and linolelaidic acids (C18:2n6c and n6t) were observed in the meat of GY than in FC and FY, which was due to the lower content of C18:2 in grass than in concentrate feed ( 81 ), as C18:2n6c in meat is derived wholly from dietary intake ( 82 ).…”
Section: Discussionsupporting
confidence: 93%
“…The proportion of elaidic FA ranged from 0.64% (RBxMN lambs) to 1.7% (MN lambs) of total FA. Higher values were reported in Santa Inês lambs (2.43%) (Lôbo et al, 2013) and Nellore beef (2.9%) (Feitosa-Braga et al, 2017) in this FA. If one considers the MUFA ratios that were found in this study, and the theoretical basis that was supported, it can be suggested that the RBxMN breed shows a health advantage compared with other breeds and species.…”
Section: Discussioncontrasting
confidence: 47%
“…However, this difference was later minimized at lambing by the FLU treatment. The effect of genetic group on body condition score at lambing seems to reflect differences in predisposition to carcass fat deposition, which occurs to a greater extent in Brazilian Somalis animals in relation to the Morada Nova (LÔBO et al, 2014). The greater live weight and body condition score of ewes that lambed two and three lambs per birth in the pre-breeding season and the live weight in later events may have been an effect of their improved nutritional status influencing the number of viable lambs leading up to lambing.Incontrast, the decreased body condition score at lambing with the greater number of lambs per birth is likely due to the greater nutritional requirements of ewes with twin or triplet-births.In this regard, fetal count by ultrasound at early stages of gestation (30-40 days), associated with a more refined nutritional management in the final third of gestation, can reduce the loss of body condition score due to twin pregnancies.…”
Section: Resultsmentioning
confidence: 99%